A Byzantine encyclopaedia of horse medicine : the sources, compilation, and transmission of the Hippiatrica - McCabe, Anne Elena (Oxford studies in Byzantium., 2007)
The veterinary compilation known as the Hippiatrica is a rich and little-known source of information about the care and medical treatment of horses, donkeys, and mules in late antiquity and the Byzantine period. This book provides a guide both to its intriguing contents, and to its complex textual history. - ;How were Greek texts on the care and medical treatment of the horse transmitted from antiquity to the present day? Using the evidence of Byzantine manuscripts of the veterinary compilation known as the Hippiatrica, Anne McCabe traces the journey of the texts from the stables to the medieval scriptorium and ultimately to the printed edition.